THE RISKS OF SWEET CORN AND POPCORN CONTAMINATION BY FUMONISIN FB1 PRODUCED DUE TO FUSARIUM VERTICILLIOIDES INFECTION - Marcin Wit; Piotr Ochodzki; Roman Warzecha; Piotr Goliński; Agnieszka Waśkiewicz; Ewa Mirzwa-Mróz; Wojciech Wakuliński (Acta Scientiarum Polonorum: Hortorum Cultus, 2018)
Based on two-year experiments on inoculated corn, including genotypes of sweet corn (Zea mays var. saccharata)and popcorn (Zea mays var. everta), the analysis of fumonisin FB1 content in kernels was performed. Infection degree of sweet corn was 2.00 and 2.13, which was distinctly stronger than infection of popcorn cobs (0.52 and 1.05). Despite of higher disease rating of Zea mays var. saccharata, the most dynamic increase in fumonisin FB1biosythesis was observed in kernels of Zea mays var. everta. During the two cropping seasons, the mean level of FB1 in sweet corn ranged from 0.52 to 6.94 µg g–1, while in popcorn kernels from 0.96 to 28.49 µg g–1 in the 1stand 8th week after inoculation. Botanical varieties of maize as well as physiological state of kernels, determined by the water, amylose and starch contents, influenced on infection degree by Fusarium verticillioides and level of ear contamination by fumonisin FB1. Efficiency of biosynthesis of mentioned metabolites was inversely